AB0737 Clinical Axial Involvement in Patients with Psoriatic Arthritis Is Underestimated: Impact on Burden of The Disease. Data from The Bepas Cohort. (15th July 2016) - De Vlam, K.; Lories, R.; Steinfeld, S.; Van Den Bosch, F.; Nzeusseu Toukap, A.; Malaise, M.; Taelman, V.; Van Bruwaene, F.; Van Den Berghe, M.; Lenaerts, J.; Joos, R.; Geusens, P.; et al.
Abstract : Background: Psoriatic Arthritis is often considered to be predominantly peripheral presenting with arthritis, dactylitis and enthesitis. Consequently randomized controlled trials, screening procedures for early detection and treatment strategies largely focus on peripheral disease. Axial involvement is considered less common. The BEPAS cohort (Belgian Epidemiological Psoriatic Arthritis Study) is a prospective multicenter real life cohort set up in 17 Belgian large academic and non academic rheumatology practices that offers a unique opportunity to study the axial involvement in this patient group. Objectives: (1) To estimate the prevalence of axial involvement in patients with PsA in general (2) to estimate the prevalence of inflammatory back pain in patients with PsA; (3) to estimate the influence of disease duration on spinal manifestations. Methods: Patients included in the BEPAS cohort were evaluated for the presence of a clinical phenotype indicating axial involvement, the specific presence of spinal complaints (reported by patients) and the presence of inflammatory back pain according the Rudwaleit criteria. Demographics and clinical features were recorded. BASDAI and BASMI were calculated. Results: Among the 461 recruited patients (mean age: 52.79 years (±12.29), male 57%) 157 patients (34, 1%) fulfilled the Berlin Criteria for inflammatory back pain with a higher prevalence in female patients (40, 5% vs 28, 9%, p=0.007) at inclusion.A family history of ankylosing spondylitis is reported in 3.3% of the patients. Clinical characteristics and demographics are listed in table 1 . Conclusions: The BEPAS cohort reports a substantial contribution of inflammatory axial involvement to the clinical and inflammatory burden of disease in PsA patients. Inflammatory axial involvement is a common clinical phenotype in PsA patients reporting higher disease activity and worse health status occurring more frequent in female patients, contrasting with other spondyoloartropathies. Disclosure of Interest: K. De Vlam: None declared, R. Lories Grant/research support from: MSD Belgium, S. Steinfeld Grant/research support from: MSD Belgium, F. Van Den Bosch Grant/research support from: MSD Belgium, A. Nzeusseu Toukap Grant/research support from: MSD Belgium, M. Malaise Grant/research support from: MSD Belgium, V. Taelman Grant/research support from: MSD Belgium, F. Van Bruwaene Grant/research support from: MSD Belgium, M. Van Den Berghe Grant/research support from: MSD Belgium, J. Lenaerts Grant/research support from: MSD Belgium, R. Joos Grant/research support from: MSD Belgium, P. Geusens Grant/research support from: MSD Belgium, S. Dall'Armellina Grant/research support from: MSD Belgium, I. Peene Grant/research support from: MSD Belgium, G. De Brabanter Grant/research support from: MSD Belgium, M. Van Den Berghe Grant/research support from: MSD Belgium, J. QU Grant/research support from: MSD Belgium, M. Maertens Grant/research support from: MSD Belgium, H. Leroi Employee of: MSD Belgium